The encyclopedia of native American religions an introduction - Hirschfelder, Arlene B.; Molin, Paulette (Facts on File, 1992)
This reference work covers major native North American religious systems, selected native American leaders and missionaries, ceremonies, legislation and court cases affecting native religions.
Keywords: Godsdiensten; Indianen; Indiens - Amérique du Nord - Religion - Encyclopédies; Indiens - Amérique du Nord - Rites et cérémonies - Encyclopédies; Indiens d'Amérique - Amérique du Nord - Religion - Encyclopédies; Indiens d'Amérique - Amérique du Nord - Rites et cérémonies - Encyclopédies; Indianer; Religion; Indians of North America -- Religion -- Encyclopedias; Indians of North America -- Rites and ceremonies -- Encyclopedias; Nordamerika; Enzyklopädie; Wörterbuch